The Cambridge guide to research in language teaching and learning - Brown, James Dean (Cambridge University Press, 2015)
Includes bibliographical references and index.; This book provides an up-to-date and comprehensive overview of research methods in second-language teaching and learning, from experts in the field. The Cambridge Guide to Research in Language Teaching and Learning covers 36 core areas of second-language research, organised into four main sections: Primary Considerations; Getting Ready; Doing the Research; Research Contexts. Presenting in-depth but easy to understand theoretical overviews, along with practical advice, the volume is aimed at 'students of research', including pre-service and in-service language teachers who are interested in research methods, as well as those studying research methods in Bachelor, MA, or PhD graduate programs around the world.